Income and Well-being - Ada Ferrer-i-Carbonell (Tinbergen Institute, 2002)
This paper presents an empirical analysis of the importance of 'comparison income' for individual well-being or happiness. In other words, the influence of the income of a reference group on individual well-being is examined. The main novelty is that various hypotheses are tested: importance of own income, relevance of the income of the reference group and of the distance between own income and the income of the reference group, and asymmetry of comparisons, i.e. the comparison income effect differing between richer and poor individuals. The analysis uses a self-reported measure of satisfaction with life as a measure of individual well-being. The data come from a large German panel known as GSOEP. The study concludes that the income of the reference group is about as important as own income for individual happiness, that individuals are happier the larger their income is in comparison with the income of the reference group, and that for some populations this comparison effect is asymmetric.
Keywords: I31; 330; Comparison Income; Interdependence of Preferences; Reference Group; Relative Utility; Subjective Well-Being; Einkommensverteilung; Lebensqualität; Schätzung; Deutschland; Varianzanalyse